Assessment of Nurses’ Exposure to Chronic Diseases in Thi-Qar Governorate Hospitals - tuama, alaa; qassim, wissam (Iraqi National Journal of Nursing Specialties, 2018)
Objective: To assess nurses’ exposure to hospitals chronic diseases hazards in Thi-Qar governorate, and to identify the association between nurses’ socio-demographic characteristics of age, sex, marital status, place of work, the experience and educational attainment and their exposure to the hazards of chronic diseases. Methodology: A purposive "non-probability" sample of (433) nurses who were selected from four public hospitals in Thi-qar governorate for the period from November 4th 2013 to June 8th of 2014. Results: The study results indicated that that the vast majority of participants have mild chronic diseases and health problems (86.8%), nurses’ age and years of working in nursing negatively correlate with occurrence of chronic disease, more than half of them are within 20-29 years-old, less than half of them have ≤ 5 years of working in nursing (45%), more than quarter of them work in emergency room, and less than half of those who have mild chronic diseases are preparatory nursing schools graduate (44.7%). Recommendations: Initiating a training program; especially; for newly working nurses that aim to prevent the occurrence of chronic diseases, Increase public awareness and education for Nurses workers in hospitals through posters, seminars, and medi